IL-10 inhibits transcription elongation of the human TNF gene in primary macrophages. - Smallie, T; Ricchetti, G; Horwood, N; Feldmann, M; Clark, A; Williams, L (2010)
IL-10 plays a central nonredundant role in limiting inflammation in vivo. However, the mechanisms involved remain to be resolved. Using primary human macrophages, we found that IL-10 inhibits selected inflammatory genes, primarily at a level of transcription. At the TNF gene, this occurs not through an inhibition of RNA polymerase II (Pol II) recruitment and transcription initiation but through a mechanism targeting the stimulation of transcription elongation by cyclin-dependent kinase (CDK) 9. We demonstrated an unanticipated requirement for a region downstream of the TNF 3' untranslated region (UTR) that contains the nuclear factor κB (NF-κB) binding motif (κB4) both for induction of transcription by lipopolysaccharide (LPS) and its inhibition by IL-10. IL-10 not only inhibits the recruitment of RelA to regions containing κB sites at the TNF gene but also to those found at other LPS-induced genes. We show that although IL-10 elicits a general block in RelA recruitment to its genomic targets, the gene-specific nature of IL-10's actions are defined through the differential recruitment of CDK9 and the control of transcription elongation. At TNF, but not NFKBIA, the consequence of RelA recruitment inhibition is a loss of CDK9 recruitment, preventing the stimulation of transcription elongation.